Magnetic and geochemical scanning reveals growth history of marine ferromanganese crust on Detroit Seamount, northwest Pacific since the early Miocene - Yi, Liang; Li, Yibing; Mikhailik, Pavel; Qi, Youqiang; Deng, Chenglong (Quaternary international, 2023)
The Hawaiian Chain-Emperor Seamounts is known to be one of the most active regions influenced by mantle hotspot. However, previous studies have provided limited information on the growth process and metal enrichment of marine ferromanganese crusts as indicators of post-eruption history. In this study, we conducted a geochronological and major elemental study of a hydrogenetic ferromanganese crust, from the Detroit Seamount using high-resolution magnetic and geochemical scanning. Our findings are as follows: (1) A total of 39 magnetozones are recognized in the studied section of the crust, which can be preliminarily correlated to the geomagnetic polarity timescale from chrons C1n to C5Dn. This correlation yields growth rates of 1.48–2.18 mm/Myr over the past ∼18 Myr. (2) Columnar and lamellar growth structures are identified with distinct metal enrichment patterns. A significant transition from lamellar to columnar growth occurred at ∼11.6 Ma. (3) The quantified elements can be clustered into three groups, (Mn, Cu–Co–Ni, and Al–Si), (Fe and Ti), and Ca. A strong correlation between metal enrichment in the crust and the global benthic foraminifera δ¹³C record is then observed. Based on these results, we suggest a predominant role of deep-sea redox conditions in the growth history of ferromanganese deposits on the Detroit Seamount since the Early Miocene.